The Socioeconomic Impact of Surgical Site Infections - Emmanuel Piednoir; Joan Robert-Yap; Patrice Baillet; Emilie Lermite; Niki Christou; Niki Christou (Frontiers Media S.A., 2021)
Précis: Surgical site infections are an ever-increasing phenomenon worldwide due to different factors. This brief report aimeds to highlight at a glance, for both physicians and political and institutional leaders, the economic burden of surgical site infections.Objectives: This brief report aimed to highlight the economic burden of surgical site infections (SSIs).Methods: A narrative review focusing on this subject has been carried out.Results: Surgical site infections are responsible for generating important costs. In 2017, a French cohort highlighted a mean cost of each SSI treatment to be around €1,814; the same year, the Centers for Disease Control and Prevention guidelines evaluated the mean cost caused by SSI treatment to be from $10,443 to $25,546 per SSI. This cost depends on many factors including the patient himself and the type of surgery.Conclusions: Prevention of the risk of infection is, therefore, a profitable concept for surgery that must be integrated within all healthcare managements worldwide.